Theoritical Analysis on Thermal Energy Storage using Phase Change Materials Capsules for Solar Organic Rankine Cycle Power Generation System - Jaffal, Hayder Mohammad (Nahrain University College of Engineering Journal, 2014)
This paper presents a theoretical analysis on packed bed thermal energy storage using phase change material (PCM) to improve the performance of solar organic Rankine cycle power generation system by extending its operational time demand to the night. The transient behavior of packed bed thermal energy storage using spherical capsules filled with paraffin wax as a storage unit has been studied numerically by finite difference technique for charging and discharging process .The effects of different parameters such as inlet temperature, mass flow rate, bed porosity , diameter of capsule and turbine inlet temperature have shown to be dominant parameters in determining the effective thermal efficiency of the solar ORC. It is seen that, turbine inlet temperature is plays an important role in the geometrical parameters of the packed bed .Comparison between theoretical results and experimental results of previous study for solar water heating system has been carried out where good agreement is noticed.